Delayed transfers of care for older people: a wider perspective. (26th February 2021) - Hinde, Sebastian; Bojke, Laura; Richardson, Gerry; Birks, Yvonne; Whittaker, William; Wilberforce, Mark; Clegg, Andrew
Abstract: Delayed transfers of care (DTOC), often unhelpfully referred to as 'bed blocking', has become a byword for waste and inefficiency in healthcare systems throughout the world. An estimated 2.7 million bed days are occupied each year in England by older people no longer in need of acute treatment, estimated to cost £820 million (2014/15) in inpatient care. Policy and media attention have often been drawn to this narrative of financial waste, resulting in policy setting that directly targets the level of DTOC, but has done little to put patient health first. These figures and policies portray a misleading image of the delays as primarily of concern in terms of their financial burden on acute hospital care, with little consideration given to the quantification on patient health or wider societal impacts. In spite of the multi-factorial decision-making process that occurs for each patient discharge, current evaluation frameworks and national policy setting fail to reflect the complexity of the process. In this commentary, we interrogate the current approach to the quantification of the DTOC impact and explore how policies and evaluation methods can do more to reflect the true impact of the delays.